CRISIS MANAGEMENT BASED ON INTEGRATION OF THE BUDGETING AND QUALITY MANAGEMENT SYSTEMS - P. V. Golovanov (Real Economics Publishing House, 2014)
The article covers the development of the economic-organizing mechanism of the crisis management of the industrial enterprise financial stability based on integration of the budget and quality management systems by using the system of targets and criteria of the processes effectiveness within the budgeting system.